The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1589/jpts.26.1723
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Walking Exercise on Changes in Cardiorespiratory Fitness, Metabolic Syndrome Markers, and High-molecular-weight Adiponectin in Obese Middle-aged Women

Abstract: [Purpose] The purpose of this study was to assess the effect of a 24-week exercise intervention on cardiorespiratory fitness, metabolic syndrome markers, and high-molecular-weight (HMW) adiponectin among obese middle-aged women. [Subjects] The subjects were 14 obese middle-aged women. [Methods] The exercise program involved walking at 50–60% of the maximum oxygen consumption, 3 times a week, for 24 weeks. Body composition analysis, blood pressure measurements, and blood analysis were performed before the exerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 30 publications
4
26
1
3
Order By: Relevance
“…An absence of Ad mer modulation upon training was observed by Ando et al [61] after 12 weeks of combined resistance and aerobic exercise in Japanese participants. Other studies reported an increased HMW level after 12 weeks of aerobic exercise in obese adults with insulin resistance [62] and after 24 weeks of walking in obese middle-aged women [63]. Our results showed that the HMW proportion was significantly decreased in untrained HF mice but not in trained HF mice when compared with controls.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…An absence of Ad mer modulation upon training was observed by Ando et al [61] after 12 weeks of combined resistance and aerobic exercise in Japanese participants. Other studies reported an increased HMW level after 12 weeks of aerobic exercise in obese adults with insulin resistance [62] and after 24 weeks of walking in obese middle-aged women [63]. Our results showed that the HMW proportion was significantly decreased in untrained HF mice but not in trained HF mice when compared with controls.…”
Section: Discussionsupporting
confidence: 45%
“…These discrepancies among studies could be related to the type and duration of exercise. Moreover, the different metabolic profiles observed in these studies could also have differently influenced the effect of training on Ad mer distribution [6163]. Regarding this point, Garekani et al [59] and Chang et al [64] suggested that the effect of exercise training on Ad pl could depend on the obesity of the subject.…”
Section: Discussionmentioning
confidence: 99%
“…Excess body fat and lack of exercise can trigger the onset of cardiovascular disease, diabetes, and hypertension among other problems 2 ) . However, regular physical activity can improve physical fitness and assist in the prevention and treatment of diseases related to a sedentary lifestyle and excess body fat 3 , 4 , 5 ) . Although the benefits of a regular physical activity program are well-known and widespread, there are still many people who do not engage in physical activity regularly 6 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have shown the effects of walking on body weight and body composition in perimenopausal and postmenopausal women [18][19][20][21][22][23][24][25][26][27][28] ; however, to our knowledge, there has not been a systematic evaluation of the effects of walking on body weight and fat distribution in perimenopausal and postmenopausal women. A meta-analysis is an approach in which individual study outcomes are quantitatively combined to arrive at overall conclusions regarding a body of research.…”
mentioning
confidence: 99%